PENGARUH KECERDASAN EMOSIONAL TERHADAP KERJASAMA DALAM TUGAS KELOMPOK SISWA KELAS VIII SMPN 6 PONTIANAK - Intan Sari yarso; M. Asrori; Yuline Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract Emotions and cooperation are related, the higher level of emotional intelligence, the higher cooperation in the group assignments of students. Therefore, Researchers want to find out more about how much the influence of emotional intelligence on cooperation in the assignment of VIII grade students of SMP Negeri 6 Pontianak. The general problem of this research is "Is there any influence of emotional intelligence on cooperation in the task of the VIII grade students of SMP Negeri 6 Pontianak?". The method used in this research is descriptive method with quantitative approach. While the data collection techniques used are indirect communication techniques. The form of this research is the study of relationships. The data collection tool used was a questionnaire. Based on data analysis of eighth grade students of SMP Negeri 6 Pontianak, emotional intelligence reached 86.57% in the good category and cooperation in group assignments reached 91.98% in the good category. The magnitude of the contribution of emotional intelligence to cooperation in the assignment of VIII grade students of SMP Negeri 6 Pontianak reached 31.69%, meaning that the contribution or effective contribution of emotional intelligence was 31.69%. Based on these explanations it can be concluded that there is a significant influence that is 31.69% of emotional intelligence on cooperation in the assignment of VIII grade students of SMP Negeri 6 Pontianak. Keywords: Emotional Intelligence, Cooperation in Group Assignments